AI-Powered Market Insight and the Transformation of Local Entrepreneurship: Evidence from SMEs in Purwakarta, Indonesian - Dikka Wiguna; Umar Fondoli; Dendi Saeful Bahri; Vina Prabaningtyas; Aujchara Thapjun; Iqbal Fadillah N Nazarudin (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study examines how AI-powered market insight contributes to the transformation of local entrepreneurship, focusing on SMEs in Purwakarta, Indonesia. Despite increasing digital adoption, many SMEs remain unable to utilize data for strategic decision-making. A qualitative case study approach was employed, with data collected through in-depth interviews, observation, and document analysis, and analyzed using thematic analysis supported by systematic coding procedures. The findings reveal that while SMEs are digitally active, their use of technology remains largely operational rather than strategic. Entrepreneurs rely heavily on experience-based decision-making, with limited capability to interpret and utilize market data. As a result, business strategies tend to be reactive, leading to inconsistent market visibility and limited competitiveness. The study demonstrates that the impact of AI on entrepreneurial transformation is indirect, mediated through market insight capability and decision-making processes. This study contributes to the literature by highlighting that the transformation of local entrepreneurship requires not only digital adoption but also the development of data-driven capabilities. The findings provide implications for policymakers and practitioners in designing targeted interventions to support SMEs in leveraging AI for sustainable growth..